Halal Forensics Issues Involving Three-Dimensional (3D) Printing Technology of Cultured Meat - Ahmad Syukran Baharuddini; Norma Jusofi; Mohd Ifwat Mohd Ghazali; Mohd Syafiq Alauddin; Mohammad Amir Wan Harun; Wan Abdul Fattah Wan Ismail; Lukman Abdul Mutalib; Hasnizam Hashim (Intelligentia Resources, 2024)
HALAL REVIEWS, 1(1), 3–15.